El tamaño de la porción modifica el consumo de alimento en estudiantes universitarios - Martínez Moreno, Alma Gabriela; Franco Paredes, Karina; Díaz Reséndiz, Felipe de Jesús; Cárdenas Villalvazo, Asucena; Aguilera Cervantes, Virginia Gabriela; Valdés Miramontes, Elia Herminia; López-Espinoza, Antonio (Acta Universitaria, 2011)
The objective of this study was to evaluate the effect of portion sizes on food consumptionin college students. Half of the participants were presented in one experimental sessionwith one-large size portion of food, and in a second session, with ten portions of the samefood totaling the same amount as the single portion provided in the first session. The restof the participants received the same food and portions but in the reverse order. While themen consumed more food when offered the single large portion than when offered the tensmaller portions, no significant difference in consumption was observed for the women.These findings suggest that portion size and social behavior do affect food consumptionin college students.